Experimental investigation of the use of PCM in an open display cabinet for energy management purposes. (15th October 2019) - Ben-Abdallah, R.; Leducq, D.; Hoang, H.M.; Fournaison, L.; Pateau, O.; Ballot-Miguet, B.; Delahaye, A.
Highlights: 7 kg of PCM is inserted inside a finned tube heat exchanger (HX). Characterization of impacts of HX presence on airflow and product temperature. Detailed description of PCM charging and discharging processes. PCM attenuates the temperature rise (from 2 °C to 1 °C) during 2 h compressor stop. This solution increases display cabinet flexibility for energy management purposes. Abstract: Display cabinets are widely used in supermarkets and represent an important part of their energy consumption. Adding PCM to a refrigerated display cabinet can increase its compressor cutoff time as the cold energy accumulated by PCM can replace the refrigeration system during a certain period of time. This technology can be considered as a solution to increase the electricity flexibility in order to match the demand and the production of a supply network, to manage energy flows on the grid and to boost the use of intermittent renewable energy sources. The present study is focused on the performance of the display cabinet with integrated phase change material (PCM). The PCM is selected according to the temperature range of the application. To enhance the heat transfer and facilitate the PCM melting and freezing, PCM is inserted in a heat exchanger. The experimental results show an important potential of PCM to maintain the air and product temperature when the compressor is off (up to 2 h).